Culture Into Perfusion-Assisted Bioreactor Promotes Valve-Like Tissue Maturation of Recellularized Pericardial Membrane - Amadeo, Francesco; Barbuto, Marianna; Bernava, Giacomo; Savini, Nicla; Brioschi, Maura; Rizzi, Stefano; Banfi, Cristina; Polvani, Gianluca; Pesce, Maurizio (Frontiers in Cardiovascular Medicine, 2020)
Derivation of tissue-engineered valve replacements is a strategy to overcome the limitations of the current valve prostheses, mechanical or biological. In an effort to set living pericardial material for aortic valve reconstruction, we have previously assessed the efficiency of a recellularization strategy based on a perfusion system enabling mass transport and homogenous distribution of aortic valve-derived ‘interstitial’ cells inside decellularized pericardial material. In the present report, we show that alternate perfusion promoted a rapid growth of valve cells inside the pericardial material and the activity of a proliferation-supporting pathway, likely controlled by the YAP transcription factor, a crucial component of the Hippo-dependent signalling cascade, especially between 3 and 14 days of culture. Quantitative mass spectrometry analysis of protein content in the tissue constructs showed deposition of valve proteins in the decellularized pericardium with a high variability at day 14 and a reproducible tissue maturation at 21 days. These results represent a step forward in the definition of strategies to produce a fully engineered tissue for replacing the calcified leaflets of failing aortic valves.